Updating the Cognitive Performance Scale. (January 2016) - Morris, John N.; Howard, Elizabeth P.; Steel, Knight; Perlman, Christopher; Fries, Brant E.; Garms-Homolová, Vjenka; Henrard, Jean-Claude; Hirdes, John P.; Ljunggren, Gunnar; Gray, Len; Szczerbińska, Katarzyna
This study presents the first update of the Cognitive Performance Scale (CPS) in 20 years. Its goals are 3-fold: extend category options; characterize how the new scale variant tracks with the Mini-Mental State Examination; and present a series of associative findings. Secondary analysis of data from 3733 older adults from 8 countries was completed. Examination of scale dimensions using older and new items was completed using a forward-entry stepwise regression. The revised scale was validated by examining the scale's distribution with a self-reported dementia diagnosis, functional problems, living status, and distress measures. Cognitive Performance Scale 2 extends the measurement metric from a range of 0 to 6 for the original CPS, to 0 to 8. Relating CPS2 to other measures of function, living status, and distress showed that changes in these external measures correspond with increased challenges in cognitive performance. Cognitive Performance Scale 2 enables repeated assessments, sensitive to detect changes particularly in early levels of cognitive decline.